2020
DOI: 10.1155/2020/3942439
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis, Assessments, and Management of Chemotherapy-Related Cognitive Impairment (CRCI): An Updated Literature Review

Abstract: There are various cancer treatments at present, and chemotherapy is one of the main methods. Chemotherapy-related cognitive impairment (CRCI), as one of the side effects of chemotherapy, has gradually attracted the attention of more and more researchers. CRCI has been verified by subjective reports and objective neuropsychological tests so far. But oncologists’ understanding of it and its treatments are still incomplete. In this review, we mainly give a comprehensive overview of the mechanism of CRCI, then des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 122 publications
1
46
0
6
Order By: Relevance
“…As stated above, the mechanism by which taxanes cause PN is not fully elucidated, although axonal damage has been identified in some studies. Chemotherapy-related cognitive impairment (CRCI) is another side effect of chemotherapy whose etiology is not well identified but appears to be related to impaired white matter integrity [ 44 ]. Moreover, neuroinflammation seems to be another possible explanatory mechanism for cognitive impairment and peripheral neuropathy, as highlighted both in clinical and animal studies [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, the mechanism by which taxanes cause PN is not fully elucidated, although axonal damage has been identified in some studies. Chemotherapy-related cognitive impairment (CRCI) is another side effect of chemotherapy whose etiology is not well identified but appears to be related to impaired white matter integrity [ 44 ]. Moreover, neuroinflammation seems to be another possible explanatory mechanism for cognitive impairment and peripheral neuropathy, as highlighted both in clinical and animal studies [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A growing evidence base supports the lasting impact of cancer and its treatment on cognitive function [5][6][7][8] . Cognitive functions typically affected are memory, attention, executive function, and processing speed 9 , resulting in negative impacts on quality of life 10 .…”
Section: Cognition and Cancermentioning
confidence: 99%
“…In addition to specifying treatment regimen, cancer type, gender, age at diagnosis, time since end of active treatment, and comorbidities, studies of cognitive function should characterize risk factors associated with lower cognitive function such as PTSD, fatigue, and childhood trauma and stress 7,21,65,66 . This is particularly important as PTSD and fatigue are highly prevalent in AYA cancer survivors.…”
Section: Well-characterized Participant Samples and Control Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a randomized controlled trial found that 2 mg of prolonged (time-released) melatonin in Alzheimer's Disease patients improved cognitive function with significant reversal of circadian disruption [33]. Tellingly, from a variety of malignancies, we know that chemotherapy is neurotoxic and that there are both acute and delayed adverse side effects of chemotherapy on cognitive function, with the resulting cognitive impairment a source of considerable distress, compromising the patient's QoL -with as much as 75% of breast cancer patients affected [38] in part mediated by oxidative stress associated with chemotherapy and by decreased hippocampal volume and cytokine-mediated blood brain barrier disruption [38][39][40], with some of these contributory neuroinflammatory cascades being triggered in many cases both by the cancer itself as well as the chemotherapy regimens deployed. It is important to note that optimal dosing matters, this being set at 20 mg nightly [39], as witness an earlier RCT [41] that failed to find any effect of melatonin on cognitive function, but the difference being it dosed at 6 mg.…”
Section: Melatonin -Neurocognitive Impact and Issuesmentioning
confidence: 99%